Complete mitochondrial genome of a tropical sea cucumber, Stichopus chloronotus. Issue 10 (3rd October 2021) - Chen, Xiaoying; Sun, Yuping; Zhao, Hongxia; Hu, Junru; Chen, Bing; Li, Huo; Huang, Wen
Abstract: In this study, we report the complete mitochondrial genome of Stichopus chloronotus. The mitogenome was 16, 247 base pairs (58.55% A + T content) in length, comprising a total of 37 genes, including 13 protein-coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. To resolve the phylogenetic position of S. chloronotus, we analyzed all mitochondrial protein-coding genes from 27 species within the Echinodermata. The results showed that S. chloronotus belonged to the family Stichopodidae and was more closely related to tropical Stichopus species ( S. horrens and S. monotuberculatus ) than to other species. Our results will be useful for evolutionary analysis of sea cucumber species.